Treaty making in Caribbean law and practice : the question of parliamentary participation - Anderson, Winston (1998)
Presents the strengths and weaknesses of the Ratification of Treaties Act, 1987 passed by the Parliament of Antigua and Barbuda, and thereby indicates the stage reached by Caribbean societies in the democratization of treaty making. Deals with the constitutional entrenchment of parliamentary participation in treaty formation. Describes the common law exercise of treaty making.